Audio-Visual Media and Practice Style Implementation to Improve Proper Ways of Tooth Brushing in Health Education Lessons - Gunawan, Rahmat; Harpinus, Doki; Maryadi, Wendri; Giovanni, Krisno; Putra, Jeki Purnama (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
The purpose of this research is to improve proper ways of tooth brushing through the implementation of audio-visual media and practice style in health education. The methodology used in this research is class action research (CAR), which the subject of the research is primary students of class 1-A in SD Labschool UPI Bandung with a total of 24 students, namely 10 male and 14 female students. Research process is divided into two cycles. The first cycle is consisted of two actions and the second cycle is consisted of one action. Every action of this research applies practice style as a way of teacher to provide opportunities for students in practicing the information which comes from audio-visual media throughout the lessons. The data is taken by filling observation form on how to brush the teeth. All the collected data is analyzed using percentage frequency distribution. From preliminary observation to the first action of second cycle, the result indicates that students are able to display proper ways of brushing teeth throughout the learning process. An increase is shown from 69,9% of students to 97,8% students that demonstrate the correct ways of brushing teeth from the starting point. Therefore, this research is proven to be successful and needs no continuation as it has achieved the desired outcomes.